Kinerja Kader Jumantik dan Pelaksanaan G1R1J terhadap Keberadaan Jentik Selama Pandemi COVID-19 di Padukuhan Santren - Elsa Nurdyah Puspitarini; Tri Wahyuni Sukesi (Politeknik Negeri Jember, 2022)
Dengue Hemorrhagic Fever is still a health problem in the midst of the COVID-19 pandemic. The most effective vector control for dengue fever is by implementing the eradication of mosquito nests by the entire community. Jumantik cadres are larvae monitoring officers and have the duty and responsibility to mobilize the community in the implementation of eradicating mosquito nests. The implementation of 1 home 1 jumantik (G1R1J) aims to involve the role of family members in larva monitoring and independent PSN. The purpose of the study was to determine the relationship between the performance G1R1J with the existence of larvae during the COVID-19 pandemic in Santren, Caturtunggal Village, Depok District, Sleman Regency. The type of research was quantitative with cross-sectional design and Chi-square analysis. Sampling obtained by cluster random sampling technique. The research was conducted in October 2021 in the area of RW 1,2,3 Santren Caturtunggal Depok Sleman.The results of the bivariate test showed that there was no relationship between the performance of jumantik cadres (p-value = 0.589> 0.05) and the implementation of G1R1J (p-value = 0.384> 0.05) and the existence of larvae during the COVID-19 pandemic in Santren, Caturtunggal Village, Depok District, Sleman Regency.There is no relationship between the performance of jumantik cadres and implementation of G1R1J with the existence of larvae during the COVID-19 pandemic in Santren Caturtunggal Depok Sleman